2018
DOI: 10.1523/jneurosci.3629-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of LFP Power and Tuning in the Frontal Cortex during Memory

Abstract: Working memory, the ability to maintain and manipulate information in the brain, is critical for cognition. During the memory period of spatial memory tasks, neurons in the prefrontal cortex code for memorized locations via persistent, spatially tuned increases in activity. Local field potentials (LFPs) are understood to reflect summed synaptic activity of local neuron populations and may offer a window into network-level processing. We recorded LFPs from areas 8A and 9/46 while two male cynomolgus macaques ()… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
0
21
2
Order By: Relevance
“…First, since LFP [6][7][8][9][10] and latent dynamics 20,21,27 are shaped by the circuit biophysics (Figure 1B), we expect to find a robust relationship between these two signals. Second, this relationship should be frequency-dependent, because only specific LFP bands are strongly correlated with the behaviour [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]51 . Third, given that the synaptic connections remain stable in the short time scale spanning the preparation and execution of a movement, we anticipate the various LFP-latent dynamics associations would remain similarly stable throughout these two processes underlying behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, since LFP [6][7][8][9][10] and latent dynamics 20,21,27 are shaped by the circuit biophysics (Figure 1B), we expect to find a robust relationship between these two signals. Second, this relationship should be frequency-dependent, because only specific LFP bands are strongly correlated with the behaviour [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]51 . Third, given that the synaptic connections remain stable in the short time scale spanning the preparation and execution of a movement, we anticipate the various LFP-latent dynamics associations would remain similarly stable throughout these two processes underlying behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Currents through these same connections are the main contributors to the generation of the LFPs 6-10 (Figure 1A). In particular, correlations in the synaptic input currents across the population yield changes in LFP power at specific frequency bands, which often relate to specific brain functions [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . For example, in the motor cortices, movement-related information lies primarily at low and high frequencies [36][37][38][39] (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This gives support to hence our external source of beta frequency entrainment from rTMS over the same region may have impaired recognition memory performance by lessening natural processes of de-synchronization as this hypothesis predicts. Holmes et al (2018) also showed a dissociation between LFP beta power and mnemonic tuning and whilst in a spatial task this is also consistent with de-synchronization aiding memory stability (Holmes et al, 2018). Neural attractor network modeling (Compte et al, 2003), in the context of delayed response task performance in NHPs, also suggests mechanisms by which a drop in LFP power may relate to memory processing; asynchronous networks can maintain memory coding for longer durations whereas synchronization leads to an overall instabilities incompatible with stable memory-coding states.…”
Section: Discussionmentioning
confidence: 56%
“…A rationale, based on information theory, is that synchronization of neural firings reduces the richness of information transfer which results in information redundancy; in contrast, a desynchronization of neural firing patterns leads to more potential for carrying information to improve the efficiency of neural communications (Simon Hanslmayr et al, 2012). The desynchronization hypothesis, applied to human recognition memory and our paradigm, maintains that a decrease of alpha/beta power may be associated with more efficient encoding, which helps contribute to successful memory retrieval subsequently (Simon Holmes et al, 2018). Therefore we first hypothesized that in our human investigations of a similar task to that performed by the NHP (albeit with lists of samples followed by lists of choice trials to increase memory demands so to avoid ceiling effects) that interfering in efficient beta desynchronization would be deleterious to successful encoding and hence recognition performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation